Records, trust, and misinformation: Using birtherism to understand the influence of conspiracy theories on human information interactions. (28th June 2022) - Donaldson, Devan Ray; LeFevre, Colin Bradley
Abstract: Records are persistent representations of activities created by partakers, observers, or their authorized proxies. People are generally willing to trust vital records such as birth, death, and marriage certificates. However, conspiracy theories and other misinformation may negatively impact perceptions of such documents, particularly when they are associated with a significant person or event. This paper explores the relationship between archival records and trustworthiness by reporting results of a survey that asked genealogists about their perceptions of 44th U.S. President Barack Obama's birth certificate, which was then at the center of the "birtherism" conspiracy. We found that although most participants perceived the birth certificate as trustworthy, others engaged in a biased review, considering it not trustworthy because of the news and politics surrounding it. These findings suggest that a conspiracy theory can act as a moderating variable that undermines the efficacy of normal or recommended practices and procedures for evaluating online information such as birth certificates . We provide recommendations and propose strategies for archivists to disseminate correct information to counteract the spread of misinformation about the authenticity of vital records, and we discuss future directions for research.